Real-time deterministic prediction of wave-induced ship responses based on short-time measurements. (1st February 2021) - Takami, Tomoki; Nielsen, Ulrik Dam; Jensen, Jørgen Juncher
Abstract: This paper studies real-time deterministic prediction of wave-induced ship motions using the autocorrelation functions (ACFs) from short-time measurements, namely the instantaneous ACFs. The Prolate Spheroidal Wave Functions (PSWF) are introduced to correct the large lag time errors in the instantaneous sample ACF, together with a modification of the autocorrelation (AC) matrix for ensuring its positive definiteness. The validity of the PSWF-based ACFs is first examined by using the ship motion measurements from model experiment under stationary wave excitations. It is shown that the use of PSWF-based ACFs leads to better prediction accuracy than direct use of sample ACFs. The validation is then extended to ship motion prediction using in-service data from a container ship, and an improvement of the prediction accuracy by PSWF-based ACFs is again found. Finally, the effectiveness of use of the instantaneous ACFs for non-stationary wave-induced responses is highlighted by comparing with the prediction results based on the ACFs from long-time measurements. Highlights: Real-time prediction method of wave-induced ship motions is addressed. Prolate Spheroidal Wave Functions (PSWF) are introduced to correct autocorrelations. Improvement of prediction accuracy by PSWF-based autocorrelations is presented. Effectiveness of short-term autocorrelation on non-stationary measurements is shown.